Financial Speculation or Capital Investment? Evidence From Relationship Between Corporate Financialization and Green Technology Innovation - Huang, Zhehao; Li, Xue; Chen, Shuanglian (Frontiers in Environmental Science, 2021)
In this paper, 3493 non-financial listed companies in China from 2007 to 2018 are selected as samples to study the impact of corporate financialization on green technology innovation through the panel regression model as well as the mediating effect model, so as to identify whether enterprises tend to financial speculation or capital investment. The main conclusions are as follows. First, corporate financialization has a speculative tendency instead of strategic capital investment. Second, corporate financialization shows heterogeneous impact on green technology innovation, which is dominated by capital expenditure. Third, the heterogeneity is reflected in two aspects: attribute characteristics and external environment. The attribute characteristics of the enterprise includes whether the industry belongs to pollution industry and the ownership structure. The external environment includes the location of enterprise and the degree of financing constraints. Fourth, there are significant differences between attribute characteristics and external environment of enterprises in the impact of financialization decision-making behavior. The deviation caused by enterprise attributes is less than 10%, but the deviation caused by external environment is close to 80%.